Pyroelectric infrared sensor for intruder detection - Moghavvemi, M.; Seng, L.C. (2004)
Nowadays, the installation of affordable automation and security system for residential and office usage has been a necessity in line with the increasing number of break-in cases in urban city. The demand for the mentioned installation is going to increase rapidly in near future. The crux of providing such systems is the occupancy map of interested areas. The occupancy map will overlook the status of the protected areas. Hence, most of the security systems nowadays have the tendency of providing occupancy map of the designated areas. In most of the security systems, presence detectors are used to achieve a secured home or office. Passive infrared detector is widely used in the presence detector as a mean of human detection. This paper discusses the application of pyroelectric infrared sensor (PIR) and the application of processing algorithm in handling sensor information so as to provide real time occupancy map on computer in control unit. PIR sensor is used to detect the presence of human in a protected room. Wireless communications network by using frequency modulation technique is developed to handle data transmission through the air. The personal computer plays a significant role in providing the intelligent centralized controls of the entire system. A software package has been developed for visual display, control mechanism configuration, and embedded server-client application.